1579 Effect of COVID-19 pandemic on the Suspected Colorectal Cancer Pathway at a District General Hospital. (12th October 2021) - Connolly, T; Nicoll, J; Hall, C
Abstract: Aim: During the initial phase of the COVID-19 pandemic the British Society of Gastroenterology and Joint Advisory Group on GI Endoscopy published guidance to halt all non-emergency endoscopy. As a result, CT was used as the first-line investigation with delayed completion endoscopy. We reviewed the efficacy of this change to determine its influence on future practice. Method: All patients referred via the suspected colorectal cancer pathway (SCCP) to our district general hospital from 15/04/20-15/05/20 (during the initial COVID-19 lockdown) were included. Retrospective analysis of patient electronic records, radiology and endoscopy was performed. Results were analysed using χ² statistic. Significant incidental pathology was defined as non-colorectal pathology requiring referral to different speciality or further imaging. Results: 115 patients were included for analysis, mean age 68 years. 2/115 (1.7%) were found to have a colorectal malignancy on CT, with no further diagnoses following completion colonoscopy. CT imaging detected significant incidental pathology in 31/115 (27%). Subgroup analysis by presenting complaint showed significant pathology was most likely to be detected in those presenting with weight loss (13/36, 36.1%, p = 0.049) or anaemia (12/31, 38.7% p = 0.084). Conclusions: CT is a valuable first-line investigation in SCCP patients. In this cohort, no colorectal malignancies were missed on CT that were later detected on endoscopy and 27% of scans detected significant non-colorectal incidental pathology. Weight loss was found to have a statistically significant correlation with incidental pathology. These findings suggest CT as a possible first-line investigation in patients presenting with weight loss, anaemia or in the event of delayed access to endoscopy.